Understanding the Relationship Between Turnover Intention and Retention Drivers in a Pharmaceutical Company - Gusanto, Angelica; Rochmiati, Ida Novida; Sintiara, Monica Febe; Sibarani, Roza Marsaulina (Universitas Ciputra Surabaya, 2023)
This research aims to examine the determinant factors related to lowering turnover intention in a pharmaceutical company. The variables used in this research are succession planning (SP), employee engagement (EE), job satisfaction (JS), and turnover intention (TI). This research seeks to determine which variables are directly related to gain more insight in order to formulate the best strategy in the future. This research was conducted on a population of 2,359 employees at anIndonesian multinational pharmaceutical company. With Slovin’s determination method, the minimum required sample size is 331. However, a total sample size of 529 is obtained. The variables are analyzed with PLS-SEM. The result depicts that EE and JS have a direct effect on TI. Meanwhile, because SP influences both EE and JS but not TI, thus EE and JS may have a mediating effect.